Synthesis of Thymoquinone–Artemisinin Hybrids: New Potent Antileukemia, Antiviral, and Antimalarial Agents - Fröhlich, Tony (ACS Med Chem Lett, 2017)
[Image: see text] A series of hybrid compounds based on the natural products artemisinin and thymoquinone was synthesized and investigated for their biological activity against the malaria parasite Plasmodium falciparum 3D7 strain, human cytomegalovirus (HCMV), and two leukemia cell lines (drug-sensitive CCRF-CEM and multidrug-resistant subline CEM/ADR5000). An unprecedented one-pot method of selective formation of C-10α-acetate 14 starting from a 1:1 mixture of C-10α- to C-10β-dihydroartemisinin was developed. The key step of this facile method is a mild decarboxylative activation of malonic acid mediated by DCC/DMAP. Ether-linked thymoquinone–artemisinin hybrids 6a/b stood out as the most active compounds in all categories, while showing no toxic side effects toward healthy human foreskin fibroblasts and thus being selective. They exhibited EC(50) values of 0.2 μM against the doxorubicin-sensitive as well as the multidrug-resistant leukemia cells and therefore can be regarded as superior to doxorubicin. Moreover, they showed to be five times more active than the standard drug ganciclovir and nearly eight times more active than artesunic acid against HCMV. In addition, hybrids 6a/b possessed excellent antimalarial activity (EC(50) = 5.9/3.7 nM), which was better than that of artesunic acid (EC(50) = 8.2 nM) and chloroquine (EC(50) = 9.8 nM). Overall, most of the presented thymoquinone–artemisinin-based hybrids exhibit an excellent and broad variety of biological activities (anticancer, antimalarial, and antiviral) combined with a low toxicity/high selectivity profile.